2016
DOI: 10.1016/j.jval.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Medical Care Costs of Obesity in the United States: Systematic Review, Meta-Analysis, and Empirical Analysis

Abstract: It would be important to acknowledge variations in the magnitude of the medical cost of obesity driven by different study design and methodology. Researchers and policy-makers need to be cautious on determining appropriate cost estimates according to their scientific and political questions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
176
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(191 citation statements)
references
References 34 publications
2
176
0
3
Order By: Relevance
“…Direct medical costs are estimated to be up to 45% higher for obese (BMI ≥ 30 kg/m 2 ) individuals as compared to those for normal weight (BMI < 25 kg/m 2 ) individuals, with a crude overall estimate of 30% higher costs (125, 434, 513). A 2016 meta-analysis of studies investigating the economic burden of obesity in the United States reported that the direct medical costs of obesity was $1,910 per person annually (234), translating to nearly $150 billion on the national level (234). For diabetes, healthcare costs in 2012 amounted to $245 billion, with on average $13,700 in medical expenditures annually for each patient with diabetes (19).…”
Section: Introductionmentioning
confidence: 99%
“…Direct medical costs are estimated to be up to 45% higher for obese (BMI ≥ 30 kg/m 2 ) individuals as compared to those for normal weight (BMI < 25 kg/m 2 ) individuals, with a crude overall estimate of 30% higher costs (125, 434, 513). A 2016 meta-analysis of studies investigating the economic burden of obesity in the United States reported that the direct medical costs of obesity was $1,910 per person annually (234), translating to nearly $150 billion on the national level (234). For diabetes, healthcare costs in 2012 amounted to $245 billion, with on average $13,700 in medical expenditures annually for each patient with diabetes (19).…”
Section: Introductionmentioning
confidence: 99%
“…In many countries, public health systems are struggling to deal with the physical and psychological consequences of obesity and its concomitant illnesses, such as metabolic syndrome [2], sleep disorders [3], depression [4,5], diabetes [6], and heart disease [7]. The United States spends nearly $150 billion per year in direct health care costs related to obesity [8]. These staggering statistics reflect the fact that hundreds of millions of individuals affected by obesity have spent a significant period of time in a state of chronic energy surplus, suggesting that their brains have at some point in time failed to accurately balance food intake with their actual energy needs.…”
mentioning
confidence: 99%
“…Being obese has serious implications for health such as elevated risks for diabetes, hypertension, and ultimately premature death (Masters et al 2013; Mokdad et al 2003; Surgeon General 2001; Thompson et al 1999). The obesity epidemic also has serious economic implications, as a recent meta-analysis estimated that direct health care costs associated with obesity totaled more than $149.4 billion dollars in 2014 alone (Kim and Basu 2016). …”
mentioning
confidence: 99%